2010
DOI: 10.1038/jhg.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

The GCKR rs780094 polymorphism is associated with susceptibility of type 2 diabetes, reduced fasting plasma glucose levels, increased triglycerides levels and lower HOMA-IR in Japanese population

Abstract: It was recently reported that GCKR rs780094 was associated with fasting plasma glucose (FPG) and triglyceride (TG) levels in various ethnic populations (A allele for low FPG and high TG). An association between GCKR rs780094 and type 2 diabetes mellitus (T2DM) (A allele for low risk) has also been reported. We examined the association between GCKR rs780094 and T2DM in Japanese subjects by analyzing 488 cases and 398 controls. A meta-analysis was performed involving two previous association studies. We also ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 23 publications
3
41
1
Order By: Relevance
“…SNPs (rs780094 and rs1260326) in the GCKR gene were previously reported to be associated with metabolic disorders; [27][28][29] however, the present study did not show the association with metabolic syndrome. The C-allele of rs780094 was reported to be associated with increased fasting plasma glucose and lower triglyceride levels.…”
Section: Discussioncontrasting
confidence: 56%
“…SNPs (rs780094 and rs1260326) in the GCKR gene were previously reported to be associated with metabolic disorders; [27][28][29] however, the present study did not show the association with metabolic syndrome. The C-allele of rs780094 was reported to be associated with increased fasting plasma glucose and lower triglyceride levels.…”
Section: Discussioncontrasting
confidence: 56%
“…The majority of genetic loci for type 2 diabetes have been initially detected in populations of European descent, except for KCNQ1 [2,3], UBE2E2 [4] and C2CD4A/C2CD4B [4], which were first identified in Japanese GWAS. Among the type 2 diabetes susceptibility loci discovered in European studies, several loci, including TCF7L2, CDKAL1, HHEX, SLC30A8, KCNJ11, CDKN2A/B, IGF2BP2 and GCKR, have been confirmed as type 2 diabetes risk loci in Japanese populations [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In several genome-wide association studies, the derived "A" allele of rs780094 was found to be associated with several metabolic phenotypes in various ethnic groups. These phenotypes included higher triglycerides, reduced risk of T2DM, lower fasting glucose, lower fasting insulin, lower HOMA-IR, lower HOMA-β, higher 2-h glucose on the oral glucose tolerance test, higher C-reactive protein, and increased risk of non-alcoholic fatty liver disease [4,[8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%